Increase in methemoglobin fraction due to the use of glyceryl trinitrate patches in preterm infants: a case report and literature review - Calandrino, Andrea; Vinci, Francesco; Battaglini, Marcella; Caruggi, Samuele; Andreato, Chiara; Montobbio, Carolina; Vannati, Marianna; Minghetti, Diego; Brigati, Giorgia; Ramenghi, Luca Antonio (Frontiers in Pediatrics, 2025)
BackgroundOxidized heme iron forms methemoglobin (MeHb), impairing the oxygen-binding capability of hemoglobin molecules. Nitric oxide (NO) obtained from glyceryl trinitrate (GTN) patches can cause MeHb formation during limb ischemia topical treatment. This case reports a preterm infant treated with multiple GTN patches who developed elevated MeHb levels, a potential therapy complication.Case presentationA preterm female newborn (25 + 4 weeks, 560 g) was delivered by cesarean due to maternal HELLP syndrome and intubated for respiratory distress. After developing ischemia in her right hand and foot, GTN patches were applied, but therapy caused a peak in methemoglobin (MeHb) levels, prompting patch removal. MeHb levels normalized after 18 h, and after adjusting therapy, ischemia resolved successfully.DiscussionWe report the case of a premature IUGR infant who developed elevated methaemoglobin (MeHb) levels during topical GTN therapy for catheter-related extremity ischemia. While GTN is effective for neonatal ischemia, its dosing, and safety lack consistent guidelines. Elevated MeHb levels, noted in similar cases here reviewed, can impair oxygen exchange, especially in vulnerable preterm infants with immature skin and reduced enzyme activity.ConclusionThis case highlights the need for careful MeHb monitoring and a multidisciplinary approach to manage ischemia safely in neonates undergoing GTN therapy.